Digital Economy, Startups, And Innovation: India’s Growth Path Towards 2047 - Shilpa K Ramannagol (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The vision of a digitally empowered economy by 2047 represents a key milestone in India’s journey towards becoming a global innovation hub. This research explores the transformative role of the digital economy, startups, and innovation in shaping sustainable growth, inclusive development, and global competitiveness. By examining current trends in digital infrastructure, artificial intelligence, blockchain, and Industry 4.0 technologies, the study highlights how these advancements can create new business models, enhance productivity, and generate employment. Startups, as engines of disruption, are expected to redefine traditional sectors such as healthcare, education, agriculture, and manufacturing through scalable and technology-driven solutions. The paper also investigates policy frameworks, regulatory mechanisms, and government initiatives like “Digital India” and “Startup India,” emphasizing their potential to foster innovation ecosystems. Challenges such as digital divide, cybersecurity, and funding gaps are critically assessed, alongside strategies to overcome them. Looking ahead, the research envisions a robust digital economy by 2047 that influences entrepreneurship, innovation, and technology to position India as a leader in the global knowledge economy while ensuring equitable access and sustainable progress.